Stablewscy herbu Oksza. Między dworem i Kościołem - Kwilecki, Andrzej (Ecclesia. Studia z Dziejów Wielkopolski, 2009)
The Stablewski family were typical of the Polish nobility, whose history included outstanding personages as well as mediocre ones, was marked with achievements but also failures. The Stablewski family settled in Wielkopolska in the second half of the 17th century. They maintained lively contacts with the Church. One representative of the family, Florian Stablewski, was the archbishop of Poznań in the years 1891-1906. Irena Stablewski actively cooperated with Catholic publishers.